BEGINNER STUDENTS’ COMMUNICATION STRATEGIES IN FOREIGN LANGUAGE CLASSROOM INTERACTION - Wahyuni, Sry; Isnaeni, Isnaeni; As'ary, Muawwal Al (Universitas Negeri Makassar, 2024)
ABSTRACT Most pre-school students sometimes face some difficulties to convey their intended meaning to the listener. This is due to the students’ insufficient communicative competence. The lack of communicative competence then arises the communication strategies (CSs) to communicate effectively. It is, therefore, important to investigate the communication strategies used by beginner students in language classroom interaction. The research was to find out the kinds of communication strategies used by the students in classroom interaction. It employed qualitative research. The participants were the students of TK Mulia Bhakti Makassar. There were two classes, TK A and TK B. TK A consisted of 12 students and TK B consisted of 9 students. The data were obtained through classroom observation. The findings showed that six kinds of communication strategies mostly appeared. Those were topic avoidance, message abandonment, word coinage, appeal for assistance, circomlocution, and mime. Keywords: Beginner, communication, communication strategies, classroom interaction, foreign language teaching